If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5-(x+8)=3x-(x-12)
We simplify the equation to the form, which is simple to understand
5-(x+8)=3x-(x-12)
Remove unnecessary parentheses
5-1x-8=3x-(x-12)
Remove unnecessary parentheses
5-1x-8=3x-1x+12
We move all terms containing x to the left and all other terms to the right.
-1x-3x+1x=+12-5+8
We simplify left and right side of the equation.
-3x=+15
We divide both sides of the equation by -3 to get x.
x=-5
| x+x/3=4 | | 35v+42-36v-12=28 | | 6m=3(5m+18) | | 4a-2b=-20 | | 12=x*.4 | | 6x+1=x | | -3.5=5x | | 6xy-12=0 | | 8=4n+12 | | -4x^2+9x+28=0 | | 6x^2+x=-2 | | 1/4(2y+1)+1/3=-y/3 | | 25+x=10 | | -3(3p+3)-2(6-14p)=3(1+6p) | | 2x+2=34x | | 2x+0.4=18 | | (3x+6)/12=10 | | -2(x-4)=4(2x-3) | | 6x-3x+5=35 | | X+1/2=2x-1/5 | | x+75=125 | | 3/10b-(1/10b-10) | | 2(f+3)+4f=6+6t | | -(7-4x)= | | x-75=125 | | 2(4x+8)=5(x-7) | | x-175= | | x^2+x^2+14x+49=4x^2+4x+1 | | r(x)=6x | | 2.8(3x-2)=-12.32 | | (-12x+6)+(4x-12)= | | 4+7x=-9x+5 |